High hopes - London, Tony, 1944-; Rabgyal, Nawang; Library of Tibetan Works & Archives (Dharamsala, H.P., [India] : Library of Tibetan Works & Archives, 2016)
"High Hopes is the story of Tibetan education in India since the arrival of Tenzin Gyatso, the Fourteenth Dalai Lama in India in 1959. When His Holiness the Dalai Lama arrived in India, he came with his retinue and many thousands of followers who arrived soon after. Their arduous journey was to a country about which most of them were ignorant. They came as deeply committed Buddhists and with a positive belief in the future. Other than the monks and high officials, most of them had little or no formal education or experience. They arrived into a country which was still emerging and forming its own identity, and still reeling from the 'Partition' and all of the related changes that had taken place after the departure of the British 'Raj'. This relatively small group of Tibetans were strangers in the political landscape of the sub-continents, with its millions. Somehow Nehru and the Indians found a way to accommodate the Tibetans. This book traces that story and the way that Tibetans in-exile have been able to forge their own unique Buddhist way of life and to incorporate that into their path for the future."--Back cover.
Includes bibliographical references (pages [321]-329) and index.
Keywords: Refugees, Tibetan -- Education -- India; Refugees, Tibetan -- Education -- Government policy -- India